ISLAMIC PERSPECTIVES ON CLAW MACHINE TRANSACTIONS - Ramadhani, Mutia; Emrizal, Emrizal; Zulkifli, Zulkifli (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2024)
: This study examines the practice of buying and selling dolls through claw machine games from the perspective of Islamic law. The research aims to explore the procedures involved in these transactions and evaluate their compliance with Islamic jurisprudential principles. A qualitative, descriptive field research method was employed, with data collected through interviews and documentation. Primary data sources include interviews with one claw machine provider and four users, while secondary sources comprise scholarly journals, articles, and books related to buying and selling practices and claw machine games. The findings reveal that the transaction begins with the purchase of a coin for IDR 1,000, which is then inserted into the claw machine to operate the controls for 30 seconds. Players attempt to maneuver the claw to grab a doll, but the outcome depends on chance, as the success of obtaining the doll is not guaranteed. From an Islamic perspective, this practice is problematic due to the presence of gharar (uncertainty) and maysir (gambling-like elements), which violate the principles of transparency, fairness, and certainty required in trade. The study concludes that the buying and selling of dolls through claw machine games is impermissible in Islam, as it fails to meet the essential conditions of valid trade and includes prohibited elements of uncertainty and chance. This research underscores the need for adherence to ethical and transparent trade practices in accordance with Islamic law.